2018
DOI: 10.14419/ijet.v7i4.44.26965
|View full text |Cite
|
Sign up to set email alerts
|

Implementation IoT in System Monitoring Hydroponic Plant Water Circulation and Control

Abstract: Hydroponics is the cultivation of plants by utilizing water without using soil by emphasizing the fulfillment of nutritional needs for plants. Deep Flow Technic (DFT) is a type of hydroponics that implements a continuous flow of nutrients and there is a pool of half of the diameter of the pipe that inundates the roots of the plant. A common obstacle experienced by DFT is the lack of maintenance of plant growth elements such as water circulation, light intensity, temperature, humidity and pH of the water which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…Plant height and leaf width were used as a reference to measure the growth of mustard plants. This refers to a similar study conducted by [27], where the measurement of the growth of the mustard plant is seen from the height of the mustard plant. The measurement of the height of the mustard plant was also carried out so that result of this research could compare the performance with similar researches.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…Plant height and leaf width were used as a reference to measure the growth of mustard plants. This refers to a similar study conducted by [27], where the measurement of the growth of the mustard plant is seen from the height of the mustard plant. The measurement of the height of the mustard plant was also carried out so that result of this research could compare the performance with similar researches.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…Research [18] discusses the Deep Flow Technique (DFT) hydroponic system by connecting IoT. The study used the fuzzy Sugeno method to combine the IoT system to create a water circulation system in hydroponic plants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In implementing the DFT hydroponic system, hydroponic circuits are made in pipes measuring 107 x 30 x 40 cm as a place to put bok choi [18]. The pipe is equipped with a water container for water circulation and an aquarium water pump to deliver nutrient water into the pipe to plant the bok choi.…”
Section: A Implementationmentioning
confidence: 99%
“…When the water level does not match the needs of the plant, the system will add water to the plant through a water pump. The experimental results showed that the air and nutrient control system could produce better growth for lettuce and bok choy plants in leaf size and plant height [3], [7], [8]. Plants in two hydroponic systems produce less water and are more air efficient with lower use of air products than plants grown in soil [9].…”
Section: Introductionmentioning
confidence: 99%